Vernon Lee’s travel essays and the “confusion” of optical and temporal lines - Claire McKEOWN (E-REA)
Vernon Lee’s response to impressionism is mixed, but in Limbo she lauds the impressionist painters’ ability to capture “the confusion of Nature’s effects.” This article builds on the idea of impressionist confusion in Vernon Lee’s travel writing, placing her comments on visual art in parallel with her treatment of place. I attempt to identify the intermedial effects and types of confusion in her texts, which are both optical— mirroring visual art—, and emotional— focusing on her subjective impressions. Her texts play with temporal strata, blending past and present through descriptions of geographical exploration. She also includes a didactic aspect in her texts, aiming to convert her readers to the idea of “sentimental travel,” which focuses on the emotions inspired by places. Reading Lee through impressionism makes it possible to extend the idea of confusion in her texts beyond her reception of impressionism, making it a guiding principle for her representation of travel as a spiritual experience.